Apathy and Emotion-Based Decision-Making in Amnesic Mild Cognitive Impairment and Alzheimer’s Disease - Sophie Bayard; Jean-Pierre Jacus; Stéphane Raffard; Marie-Christine Gely-Nargeot (Behavioural Neurology)
Background. Apathy and reduced emotion-based decision-making are two behavioral modifications independently described in Alzheimer’s disease (AD) and amnestic mild cognitive impairment (aMCI). Objectives. The aims of this study were to investigate decision-making based on emotional feedback processing in AD and aMCI and to study the impact of reduced decision-making performances on apathy. Methods. We recruited 20 patients with AD, 20 participants with aMCI, and 20 healthy controls. All participants completed the Lille apathy rating scale (LARS) and the Iowa gambling task (IGT). Results. Both aMCI and AD participants had reduced performances on the IGT and were more apathetic compared to controls without any difference between aMCI and AD groups. For the entire sample, LARS initiation dimension was related to IGT disadvantageous decision-making profile. Conclusions. We provide the first study showing that both aMCI and AD individuals make less profitable decisions than controls, whereas aMCI and AD did not differ. Disadvantageous decision-making profile on the IGT was associated with higher level of apathy on the action initiation dimension. The role of an abnormal IGT performance as a risk factor for the development of apathy needs to be investigated in other clinical populations and in normal aging.